Search Rate and Functional Response of a Eusocial Insect (Oecophylla longinoda) in a Tanzanian Mango Orchard - Thora Samsø Fast; Jørgen Aagaard Axelsen; Gina Kier Lynegaard; Maulid Mwatawala; Joachim Offenberg (Psyche: A Journal of Entomology)
Weaver ants, Oecophylla spp., are famous for being efficient biological control agents as they prey on a variety of insects, and they are capable of suppressing a large number of pest species. Here, the search rate and functional response of Oecophylla longinoda were investigated in a Tanzanian mango orchard using feeding experiments. This was done by following the removal of prey, which constituted the foundation for estimating the search rate by aid of the Nicholson-Bailey and Lotka-Volterra models. The overall mean search rate was 3.2 ×10-4 and 1.7 ×10-4 over 30 minutes, when calculating the search rate using the Nicholson-Bailey equation and the Lotka-Volterra equation (modified Holling equation), respectively. The functional response investigations showed a linear relationship between removed prey and available prey, suggesting type I functional response or, alternatively, the initial phase of type II functional response. The results presented here are probably the first attempt to identify the functional response type of a colony of living predatory eusocial insects.